Several regulations in gravity table in quality of tobacco seeds - Gadotti,Gizele I. (2012)
The use of gravity table can result in improved quality of seeds of several species, demonstrating the superiority of the quality attributes of seeds collected in the top positions in relation to the lower positions of the discharge zone of the gravity table. The availability of information on tobacco seeds, particularly on the action of gravity table, has not been addressed in the literature. The present study was to evaluate the influence of different regulations in the gravity table on the quality of tobacco seeds. The terminal edge of the machine of 50 cm width was divided into four parts plus the outlet for stones. The treatments were in the following fractions: original seed (obtained in the feed hopper), heavy seed (at the top), middle high, intermediate, and light seed (lower part), and the stones outlet of the gravity table. Each combination of regulation was in an independent adjustment with a total of seven adjusts. The gravity table, in the adjustments with high oscillation, was efficient in improving the physiological quality of seed lots of tobacco, by removing the fraction of light seeds discharged at the bottom of the terminal edge.